2022
DOI: 10.3390/su14159279
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Motivational and Technological Factors Influencing Massive Open Online Courses’ Continuous Intention to Use

Abstract: Massive open online courses have been regarded as effective technological innovations that improve educational systems in the era of digitalisation. However, only 10% of the registered students complete their courses. This study aims to examine the motivational and technological factors and contextual features on students’ continuous intention to use. A questionnaire was gathered from 315 of students in the UAE and revealed that social motivational and technological factors driven by the technology acceptance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In contrast to traditional knowledge management systems, the peer-to-peer learning approach allows participants to actively and flexibly share their knowledge [30]. In developing country contexts, MOOCs bridge the educational gap among learners regardless of their socioeconomic status by providing openly accessible education with minimal or no fees [31].…”
Section: Capacity Development and Knowledge Management In Transbounda...mentioning
confidence: 99%
“…In contrast to traditional knowledge management systems, the peer-to-peer learning approach allows participants to actively and flexibly share their knowledge [30]. In developing country contexts, MOOCs bridge the educational gap among learners regardless of their socioeconomic status by providing openly accessible education with minimal or no fees [31].…”
Section: Capacity Development and Knowledge Management In Transbounda...mentioning
confidence: 99%
“…According to Al-Rahmi et al (2021b) , the majority of respondents had positive attitudes when it came to using MOOC platforms, demonstrating that MOOCs are believed to be successful in enhancing conceptual knowledge throughout teaching-learning activities. According to previous research ( Al-shami et al, 2022 ), attitude is the most effective predictor of the desire to utilize technology. Employing a Chinese sample ( Luo et al, 2021 ), the attitude toward MOOCs and perceived behavioral control (PBC) were revealed to be important drivers of the intention to utilize them.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…According to previous research (Al-shami et al, 2022), attitude is the most effective predictor of the desire to utilize technology. Employing a Chinese sample (Luo et al, 2021), the attitude toward MOOCs and perceived behavioral control (PBC) were revealed to be important drivers of the intention to utilize them.…”
Section: Attitude Toward Using Moocsmentioning
confidence: 99%